PERFORMANCE ANALYSIS OF BADAN AMIL ZAKAT NASIONAL (BAZNAS) IN MANAGING ZAKAT IN PAREPARE CITY - Rukmana, Nur Aisya Rukmana (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2025)
This research discusses the performance of the National Amil Zakat Agency (BAZNAS) in managing zakat in Parepare City. The purpose of this study is to analyze in depth the performance of BAZNAS in the process of collecting and distributing zakat, as well as to evaluate the distribution system implemented in reaching the mustahik. The study also aims to assess the extent to which the effectiveness of zakat management contributes to community welfare and aligns with sharia principles. The method used in this research is a descriptive qualitative approach with a case study on BAZNAS Parepare City. Data were obtained through observation, interviews with BAZNAS internal parties, and documentation of zakat management activities. The results of the study show that the performance of BAZNAS Parepare City in zakat collection is quite productive and reliable. BAZNAS applies collection strategies through civil servant salary deductions, bank transfers, QRIS, and Zakat Collection Units (UPZ). In terms of distribution, zakat is allocated both consumptively and productively by considering the principles of justice, transparency, and empowerment. This proves that BAZNAS Parepare has carried out its role well in realizing social justice and community welfare through effective and sharia-based zakat management.